Antineoplastic agent busulfan regulates a network of genes related to coagulation and fibrinolysis. - Reimer, Janka; Bien, Sandra; Ameling, Sabine; Hammer, Elke; Völker, Uwe; Hempel, Georg; Boos, Joachim; Kroemer, Heyo; Ritter, Christoph (European Journal of Clinical Pharmacology, 2012)
Purpose: Hepatic veno-occlusive disease (HVOD) is one of the major complications following hematopoietic stem cell transplantation (HSCT). Although high-dose busulfan is associated with the development of HVOD, the underlying molecular mechanisms are still unknown. Methods: Transcriptional gene regulation by busulfan was profiled using Affymetrix GeneChip Human Genome U133 Plus 2.0 arrays. Messenger RNA (mRNA) expression of regulated genes was assessed by TaqMan real-time polymerase chain reaction (PCR), and protein expression and secretion was determined by enzyme-linked immunosorbent assay (ELISA) in cell supernatants, lysates, and patient plasma. Results: Plasma levels of plasminogen activator inhibitor (PAI)-1 significantly increased 48 h after starting busulfan treatment IV in children preconditioned for HSCT. In vitro, busulfan significantly induced plasminogen activator inhibitor-1 (PAI-1) expression in endothelium-like ECV304 cells in a concentration- and time-dependent manner. Comparative transcriptional profiling of busulfan-treated and control ECV304 cells identified differential expression of genes related to coagulation and fibrinolysis, including tissue factor, tissue factor pathway inhibitor-1, protein S, thrombospondin-1, urokinase receptor, and PAI-1, as well as activin A and transforming growth factor beta 1 (TGF-β1). Ingenuity pathway analysis (IPA) suggested TGF-β1 as a central modulator of gene regulation by busulfan. Consequently, expression of tissue factor, urokinase receptor, and PAI-1 mRNA and PAI-1 protein secretion induced by busulfan were significantly reduced by the activin A/TGF-β1 inhibitor SB 431542 in ECV304 and primary endothelial cells. Conclusions: This is the first report that directly relates busulfan exposure to antifibrinolytic activity by PAI-1 and hypercoagulation possibly mediated by members of the TGF-β1 family. This suggests further research to evaluate activin A and TGF-β1 as potential targets for HVOD treatment.